Blood pressure lowering with alcohol‐mediated renal denervation using the Peregrine infusion Catheter is independent of injection site location. Issue 6 (2nd September 2021) - Mahfoud, Felix; Bertog, Stefan; Lauder, Lucas; Böhm, Michael; Schmid, Axel; Wojakowski, Wojciech; Parise, Helen; Fischell, Tim A.; Kandzari, David E.; Pathak, Atul; Persu, Alexandre; Sievert, Horst
Abstract: Objectives: The current analysis utilized core laboratory angiographic data from a prospective, single‐arm, open‐label, multi‐center feasibility study to ascertain whether the location of alcohol infusion within main renal arteries during renal denervation (RDN) had an impact on the BP‐lowering effect at 6 months. Background: The influence of the location of alcohol infusion during RDN, within the main renal artery (proximal, middle, or distal), on the magnitude of the blood pressure (BP) lowering is unstudied. Methods: The Peregrine Catheter was used to perform alcohol‐mediated RDN with an infusion of 0.6 mL of alcohol per artery as the neurolytic agent in 90 main arteries and four accessory arteries of 45 patients with hypertension. Results: No relationship between the site of alcohol infusion and change from baseline in both office systolic and 24‐hour systolic ambulatory BP (ABP) at 6 months was observed. When analyzed at the artery level, the least squares (LS) mean changes ± SEM from baseline to 6 months post‐procedure in 24‐hour systolic ABP when analyzed by renal arterial location were −11.9 ± 2.4 mmHg (distal), −10 ± 1.6 mmHg (middle), and −10.6 ± 1.3 mmHg (proximal) (all p < 0.0001 for change from baseline within groups). The results were similar for office systolic BP. There was no difference between treated locations (proximal is reference). Conclusion: In this post‐hoc analysis, the location of alcohol infusion within the main renal artery using the Peregrine system, with alcohol as the neurolytic agent for chemical RDN, did not affect the magnitude of BP changes at 6 months.